Reactor scale study of self-heating and self-ignition of torrefied wood in contact with oxygen. (15th February 2018) - Evangelista, Brieuc; Arlabosse, Patricia; Govin, Alexandre; Salvador, Sylvain; Bonnefoy, Olivier; Dirion, Jean-Louis
Abstract: This experimental work aims at investigating the potential development of self-heating when torrefied wood chips enter into contact with oxygen. Two kilograms of dried beech chips have been torrefied under nitrogen in a cylindrical reactor at 250 °C or 285 °C. The temperature was then leveled down between 100 °C and 160 °C and nitrogen flow was replaced by oxygen-containing flow. Influences of oxygen volumetric fraction and sweeping gas flow rate were investigated. Temperatures at different bed locations and gaseous product volumetric fractions at the bed output were monitored continuously. In some of the experiments a limited temperature rise was observed while in others a temperature runaway occurred. Thermal considerations indicate a clear enhancement of self-heating propensity with the severity of torrefaction. Gas phase analysis and molecule oxygen balance reveal an adsorption mechanism pathway and a higher rate of oxygen adsorption for the severely torrefied wood. Lowering the oxygen volumetric fraction or increasing the flow rate decrease self-heating behavior and was used to stop self-ignition of the bed.